2022
DOI: 10.1038/s41467-022-35639-x
|View full text |Cite
|
Sign up to set email alerts
|

Actin-microtubule cytoskeletal interplay mediated by MRTF-A/SRF signaling promotes dilated cardiomyopathy caused by LMNA mutations

Abstract: Mutations in the lamin A/C gene (LMNA) cause dilated cardiomyopathy associated with increased activity of ERK1/2 in the heart. We recently showed that ERK1/2 phosphorylates cofilin-1 on threonine 25 (phospho(T25)-cofilin-1) that in turn disassembles the actin cytoskeleton. Here, we show that in muscle cells carrying a cardiomyopathy-causing LMNA mutation, phospho(T25)-cofilin-1 binds to myocardin-related transcription factor A (MRTF-A) in the cytoplasm, thus preventing the stimulation of serum response factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 125 publications
0
5
1
Order By: Relevance
“…Although cofilin1 and ADF have been implicated in MRTF-SRF regulation in cardiomyocytes and corneas (53)(54)(55), we found neuronal SRF activity unchanged upon inactivation of cofilin1 or ADF. Instead, SRF activity was moderately increased in ADF/Cfl1-dKO neurons, in line with studies demonstrating overlapping brain functions for both ABPs (22)(23)(24)56).…”
Section: Discussioncontrasting
confidence: 79%
“…Although cofilin1 and ADF have been implicated in MRTF-SRF regulation in cardiomyocytes and corneas (53)(54)(55), we found neuronal SRF activity unchanged upon inactivation of cofilin1 or ADF. Instead, SRF activity was moderately increased in ADF/Cfl1-dKO neurons, in line with studies demonstrating overlapping brain functions for both ABPs (22)(23)(24)56).…”
Section: Discussioncontrasting
confidence: 79%
“…Unstable sarcomere movement will lead to myocardial contraction disorder and affect intracellular signal transmission. Therefore, skeletal protein defects represent an important mechanism of DCM ( Le Dour et al, 2022 ). However, the molecular pathogenesis of LMNA -related DCM has not yet been clearly clarified.…”
Section: Discussionmentioning
confidence: 99%
“… 52 , 53 Several recent studies reported that microtubule network contributes to laminopathy pathophysiology in progeria and in dilated cardiomyopathies (DCM). 20 , 21 , 54 , 55 , 56 This effect is mediated by an increase in alpha-tubulin acetylation when compared to control cells that induce an increased microtubule network stability. 55 , 57 Moreover, the inhibition of acetyltransferase protein 10 (NAT10), responsible for alpha-tubulin acetylation, improves cellular phenotype in progeria and DCM models reinforcing the potential role of microtubule network in laminopathies.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Few other studies have addressed the effect of missense mutations, mainly mutations involved in cardiomyopathies or progeria. 18 , 19 , 20 , 21 However, the diversity of approaches has resulted in a large panel of results that are rather difficult to compare. 3 , 22 , 23 In addition, the link between lamin A/C structural or functional changes and cell or tissue manifestations in the pathological context of laminopathies remains unclear.…”
Section: Introductionmentioning
confidence: 99%